LEITURA: UM PASSAPORTE PARA LER O MUNDO “NO” E “A PARTIR DO” ENSINO SUPERIOR - Melo, Franciele Soares de (Vivências, 2019)
Reading: a passport to read the world in and from higher education. This study emphasizes the reading ability in Higher Education and through the objective of developing a reflection on the importance of reading, given that it is essential to the students’ learning and, therefore, it implies in their academic qualification and performance as a professional. It is also worth noting the importance of the teacher to for the theoretical foundations regarding the teaching of reading, in order to base his/her pedagogical action. In addition to improve the specific knowledge of the discipline, it is imperative that the teacher masters the various technological tools so that his/her pedagogical work can be completed by developing activities directing to that skill. Thus, reading is a determining factor for the improvement of competences related to the world understanding and logical criticality, which leads the individual to have an active, dynamic and responsive attitude towards the world.